Nierentransplantation im Kindesalter - Tönshoff, Burkhard; Billing, Heiko; Rieger, Susanne; Höcker, Britta (Monatsschrift Kinderheilkunde, 2012)
Renal transplantation is the optimal treatment modality for children with end-stage renal disease. Compared to chronic dialysis patient survival and quality of life can be strikingly improved. The results of paediatric renal transplantation have been improved markedly in the last 10 years. The current 5-year transplant survival rate is 90% after living donation and 82% after deceased donation. Despite this success a number of unmet relevant clinical problems remain: prevention of organ toxicity particularly by chronic rejection, development of tolerance-inducing protocols, minimisation of long-term toxicity of immunosuppressive therapy, avoidance of secondary cardiovascular comorbidity, prevention of posttransplant lymphoproliferative disease, optimisation of longitudinal growth, improvement of quality of life, enhancement of adherence to the immunosuppressive medication and improved concepts for a structured transition to adult care. Further progress can be expected through interdisciplinary collaborative approaches and through an increase in professionalised paediatric transplant medicine and accompanying clinical research.